2017
DOI: 10.2147/ott.s124321
|View full text |Cite
|
Sign up to set email alerts
|

Serum galectin-1 in patients with multiple myeloma: associations with survival, angiogenesis, and biomarkers of macrophage activation

Abstract: Galectin-1 (Gal-1) is known to regulate cell signaling within the immune system and may be a target for new anticancer immune therapy. In patients with chronic lymphocytic leukemia (CLL) and classical Hodgkin lymphoma (cHL), high levels of Gal-1 within the tumor microenvironment were associated with worse disease state or poor outcome. Gal-1 can be secreted from cells by an unknown mechanism, and levels in blood samples were associated with high tumor burden and worse disease state in cHL and CLL patients. How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Recently, Van Woensel and coworkers showed that intranasal delivery of Gal-1 siRNA induced a remarkable switch in the TME composition, reducing macrophage polarization from M1 to M2 and inhibiting recruitment of monocytic MDSCs during glioblastoma multiforme progression [122]. In this sense, Gal-1 levels positively correlated with soluble CD163, a biomarker of M2 macrophage activation in sera from multiple myeloma patients [123].…”
Section: Galectin-1 Contributes To the Immunoregulatory And Pro-tumormentioning
confidence: 99%
“…Recently, Van Woensel and coworkers showed that intranasal delivery of Gal-1 siRNA induced a remarkable switch in the TME composition, reducing macrophage polarization from M1 to M2 and inhibiting recruitment of monocytic MDSCs during glioblastoma multiforme progression [122]. In this sense, Gal-1 levels positively correlated with soluble CD163, a biomarker of M2 macrophage activation in sera from multiple myeloma patients [123].…”
Section: Galectin-1 Contributes To the Immunoregulatory And Pro-tumormentioning
confidence: 99%
“…Moreover, analyses of gene expression datasets of MM primary CD138+ cells revealed that LGALS1 (galectin-1 gene) levels are significantly higher in newly diagnosed MM (MMD) patients, but not in MGUS, SMM and MM relapsed, compared to healthy donors [ 24 , 107 ]. Recently, it has been published that, in peripheral blood sera, galectin-1 protein level was borderline significantly higher in MMD compared to healthy controls and that the levels of this lectin in peripheral blood are not associated with OS, response to treatment and clinical pathological parameters [ 108 ]; on the other hand, this study shows only a positive correlation between galectin-1 and soluble (s)CD163, a macrophage activation marker, and sCD138 [ 108 ]. Moreover, galectin-1 has been identified as a ECM-associated protein that characterizes only the MM BM and not the ECM of MGUS patients or healthy controls [ 107 ].…”
Section: Galectins and Multiple Myelomamentioning
confidence: 83%
“…The prognostic roles of galectin family members have also been studied in multiple myeloma. A previous study reported no increase in the serum LGALS1 level in multiple myeloma and no association with its prognosis (20). However, another study reported that LGALS1 expression in multiple myeloma cells was upregulated under hypoxic conditions and that downregulation significantly reduced the tumor burden in a mouse model (21).…”
Section: Introductionmentioning
confidence: 98%